A Systematic Review of Salt Reduction Initiatives Around the World: A Midterm Evaluation of Progress Towards the 2025 Global Non-Communicable Diseases Salt Reduction Target. Issue 5 (7th March 2021) - Santos, Joseph Alvin; Tekle, Dejen; Rosewarne, Emalie; Flexner, Nadia; Cobb, Laura; Al-Jawaldeh, Ayoub; Kim, Warrick Junsuk; Breda, Joao; Whiting, Stephen; Campbell, Norm; Neal, Bruce; Webster, Jacqui; et al.
Abstract: In 2013, the WHO recommended that all member states aim to reduce population salt intake by 30% by 2025. The year 2019 represents the midpoint, making it a critical time to assess countries' progress towards this target. This review aims to identify all national salt reduction initiatives around the world in 2019, and to quantify countries' progress in achieving the salt reduction target. Relevant data were identified through searches of peer-reviewed and gray literature, supplemented with responses from prefilled country questionnaires sent to known country leads of salt reduction or salt champions, WHO regional representatives, and international experts to request further information. Core characteristics of each country's strategy, including evaluations of program impact, were extracted and summarized. A total of 96 national salt reduction initiatives were identified, representing a 28% increase in the number reported in 2014. About 90% of the initiatives were multifaceted in approach, and 60% had a regulatory component. Approaches include interventions in settings ( n = 74), food reformulation ( n = 68), consumer education ( n = 50), front-of-pack labeling ( n = 48), and salt taxation ( n = 5). Since 2014, there has been an increase in the number of countries implementing each of the approaches, except consumer education. Data on program impact were limited. There were 3 countries that reported a substantial decrease (>2 g/day), 9 that reported a moderate decrease (1–2 g/day), and 5 that reported a slight decrease (<1 g/day) in the mean salt intake over time, but none have yet met the targeted 30% relative reduction in salt intake from baseline. In summary, there has been an increase in the number of salt reduction initiatives around the world since 2014. More countries are now opting for structural or regulatory approaches. However, efforts must be urgently accelerated and replicated in other countries and more rigorous monitoring and evaluation of strategies is needed to achieve the salt reduction target.